2018
DOI: 10.1007/s11060-018-2988-0
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for recurrent gliomas

Abstract: GKRS can safely be used as salvage treatment for recurrent glioma and seems to improve survival rates in (high grade) glioma patients with minimal burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
12
0
2
Order By: Relevance
“…We analyzed the data with respect to GKRS in our center and found a median PFS of 4 months and a median OS of 13 months after GKRS, indicating its efficacy in the treatment of malignant glioma. Sadik et al [10] found that the median PFS and OS were 5.7 and 12.8 months after GKRS in a cohort of 94 recurrent glioma patients without any serious complications. Imber et al [6] reported a median OS of 10.6 months in 174 glioblastoma cases after GKRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the data with respect to GKRS in our center and found a median PFS of 4 months and a median OS of 13 months after GKRS, indicating its efficacy in the treatment of malignant glioma. Sadik et al [10] found that the median PFS and OS were 5.7 and 12.8 months after GKRS in a cohort of 94 recurrent glioma patients without any serious complications. Imber et al [6] reported a median OS of 10.6 months in 174 glioblastoma cases after GKRS.…”
Section: Discussionmentioning
confidence: 99%
“…It has advantages in the management of glioma, including accurate location, a steep dose distribution gradient, a small impact on the surrounding tissue, and low cost. In a recent review, the DOI: 10.1159/000509782 longest median overall survival (OS) was found with GKRS as a salvage therapy [10]. Many doctors also use GKRS as a supplementary treatment after surgery, intensity-modulated radiation therapy, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on histogenesis and biological characteristics, a similar occurrence of neuroectodermal tumors in a variety of complex tumors is generally referred to as “glioma” 3,4. The incidence of gliomas ranges from 3 to 8 per 100,000 people in China while the global morbidity ranges from 4.67 to 5.73 per 100,000 people 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is the most common primary intracranial malignant tumor and accounts for 30% of all central nervous system tumors 1 , 2 . The World Health Organization (WHO) classification of central nervous system tumors places gliomas into grades I-IV, with grades I and II indicating low-grade gliomas and grades III and IV, high-grade gliomas (HGGs) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HGGs is approximately 5 per 100,000 person-years. Researches have shown that gliomas are more common in adults and the elderly than in children; they also occur more often in men than in women 1 , 2 , 4 , 5 . HGGs are characterized by the "three high and one low" principle: high incidence rate, high recurrence rate, high mortality, and low cure rate.…”
Section: Introductionmentioning
confidence: 99%